2010
DOI: 10.1021/ja105714r
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Domain Specific Recruitment of Lipophilic Nucleic Acids: A Key for Switchable Functionalization of Membranes

Abstract: Lipid domains in mammalian plasma membranes serve as platforms for specific recruitment or separation of proteins involved in various functions. Here, we have applied this natural strategy of lateral separation to functionalize lipid membranes at micrometer scale in a switchable and reversible manner. Membrane-anchored peptide nucleic acid and DNA, differing in their lipophilic moieties, partition into different lipid domains in model and biological membranes. Separation was visualized by hybridization with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 51 publications
2
69
0
1
Order By: Relevance
“…The studies described in this manuscript complement the research of various scientific groups whose work is focused on the formation of complex nanoarchitectures [3334], the interaction of such nanostructures with lipid membranes [3538], as well as the optimization of the in vivo delivery of lipophilic siRNA [1012] (e.g., by DNA trafficking [7]).…”
Section: Resultsmentioning
confidence: 99%
“…The studies described in this manuscript complement the research of various scientific groups whose work is focused on the formation of complex nanoarchitectures [3334], the interaction of such nanostructures with lipid membranes [3538], as well as the optimization of the in vivo delivery of lipophilic siRNA [1012] (e.g., by DNA trafficking [7]).…”
Section: Resultsmentioning
confidence: 99%
“…Loew et al demonstrated that palmitoylated peptide nucleic acids partition almost exclusively to liquid-ordered domains [66]. When combined with the L -partitioning tocopherol anchors discussed earlier, this allowed the construction of GUVs where each phase was encoded with a different DNA functionality.…”
Section: Breaking Symmetry: Phase Separation and Aspherical Structmentioning
confidence: 99%
“…3c) have also been used to stably anchor nucleic acids to membranes via two hydrocarbon chains [66].…”
Section: Double Hydrocarbon Anchorsmentioning
confidence: 99%
“…Vesicles exhibiting Janus-like morphology have also been constructed in aw ay that allowed the local confinement of DNA. [78,79] Inspired by how membrane proteins are targeted to raft domains through palmitoylation (i.e.t he post-translational addition of palmitic acid), Arbuzova and co-workers [79] were able to palmitoylate aDNA-recognizing peptide nucleic acid (PNA) with the aim of exclusively partitioning the PNA into the liquid-ordered domains of liquid-liquid phaseseparated giant unilamellar vesicles (GUVs). This strategy was highly effective and allowed the specific partitioning of lipophilic DNAa nd PNAm olecules into defined membrane environments to be combined with the reversible temper-ature-dependent intermixing of laterally separated membrane domains.…”
Section: Membrane Compositional Heterogeneitymentioning
confidence: 99%